2020
DOI: 10.1080/07038992.2020.1829462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of LiDAR Building Point Cloud with Reference Model for Deep Comprehension of Cloud Structure

Abstract: This paper studies the fidelity level of the extracted Lidar (LIght Detection And Ranging) building point cloud in relation to the original building.In this context, the building point cloud is compared with a reference model. This comparison allows a deep understanding of the point cloud structure with respect to both the actual building and the constructed model. Consequently, the source of the incompatibility in a (reference or constructed) building model is determined and described. Thus, this study consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…In fact, the undesirable points sometimes represent an obstacle to the modelling algorithms, especially when their percentage exceeds certain limits. Sometimes they are considered as the main reason for automatic modelling failure or the source for some deformations in the obtained building model [21]. Second, it considers an important case, which is the case of high trees associated with the building roof.…”
Section: Filtering Of Noisy Building Maskmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, the undesirable points sometimes represent an obstacle to the modelling algorithms, especially when their percentage exceeds certain limits. Sometimes they are considered as the main reason for automatic modelling failure or the source for some deformations in the obtained building model [21]. Second, it considers an important case, which is the case of high trees associated with the building roof.…”
Section: Filtering Of Noisy Building Maskmentioning
confidence: 99%
“…The outcome of airborne laser scanning is a 3D point cloud. This point cloud provides the input data for a series of operations that aims to classify and then model the points into their appropriate classes such as terrain, buildings and vegetation [21]. In literature, from 1995 until the present, hundreds of research papers suggested automatic approaches for achieving the automatic LiDAR data classification and modelling [28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations